Structural Barriers to Accessing the Campus Assault Resources and Education (CARE) Offices at the University of California (UC) Campuses - Mitra, Atreyi (Journal of interpersonal violence, 2022)
In order to continue pushing college campuses to the forefront of survivor-centered practice and student-centered care, it is imperative that the barriers students experience in accessing campus sexual violence resource centers be documented and addressed. This research evaluates student and staff perceptions of barriers to accessing the Campus Assault Resources and Education (CARE) offices on three University of California (UC) campuses. Data were collected by researchers from UC Speaks Up, a cross-campus research initiative at UC Los Angeles (UCLA), UC Santa Barbara (UCSB), and UC San Diego (UCSD) aimed at understanding factors that both contribute to and prevent sexual violence among college students. This analysis only included data that yielded insights into CARE?s accessibility. Thematic analysis of 63 interviews and 27 focus group discussions was conducted using Dedoose. The following six thematic codes emerged from the data: (1) awareness of office, (2) confidentiality of services, (3) physical accessibility, (4) accessibility for vulnerable and marginalized groups, (5) utilization experiences, and (6) limited institutional support. To increase the accessibility of sexual violence resource centers in higher education, this study indicates that universities and campus sexual violence resource centers should (1) encourage survivor-centered cross-campus collaborations between sexual violence resource centers and other campus entries, (2) add more trainings that are tailored to the needs of vulnerable and marginalized communities, (3) increase the resource?s campus-wide office exposure through multiple prevention education opportunities, and (4) better fund sexual violence resource centers. Implications for future research are discussed to maximize this study?s public health impact.